Pre-harvest application of fungicides influences the post-harvest quality of cauliflower (Brassica oleracea var. botrytis L.) - Monteiro, Gean C. [UNESP]; da Silva, Mônica B. [UNESP]; Rodrigues, Luan F.O.S. [UNESP]; Gomez-Gomez, Hector A. [UNESP]; Borges, Cristine Vanz [UNESP]; Minatel, Igor O. [UNESP]; Lima, Giuseppina P.P. [UNESP] (Southern Cross Publishing, 2019)
Two cauliflower cultivars (cv.) (Flamenco and Verona) were treated with fungicides (boscalid (Cantus ®)) (0.3 g L-1), pyraclostrobin + fluxapyroxad (Orkestra ® SC) (0.3 mL L-1), metiram + pyraclostrobin (Cabrio ® Top) (3.0g L-1) and metiram + pyraclostrobin + boscalid (Cantus ® + Cabrio ® Top) in order to evaluate their chemical composition and their influence on post-harvest quality. The fungicides were applied during the seedling stage as well as 30 days before harvest. Freshly harvested inflorescences were analyzed at 3-day intervals for up to 12 days in storage (10 ± 2 °C and 92 ± 2 % RH) to verify the polyamine content, peroxidase and polyphenoloxidase activities and physicochemical attributes. All fungicides induced changes in polyamine metabolic pathways, resulting in increased levels of spermidine and spermine. These compounds may be related to the reduced activity of polyphenoloxidase and peroxidase and to cauliflower senescence. Pre-harvest application of metiram + pyraclostrobin + boscalid to cv. Flamenco and of fluxapyroxad + pyraclostrobin to cv. Verona were found to be the most efficient treatments for improving the commercial quality of cauliflower. No levels of the fungicides applied during the cultivation were detected in the post-harvest. The fungicides applied to the pre-harvest effectively prolong the storage time and visual quality of cauliflowers cv. Flamenco and cv. Verona.
Keywords: Boscalid; Enzymatic activity; Metiram; Polyamines; Strobilurin; Visual quality